2007
DOI: 10.1002/dneu.20558
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of actomyosin contractility by PI3K in sensory axons

Abstract: Phosphatidylinositol 3-kinase (PI3K) activity is known to be required for the extension of embryonic sensory axons. Inhibition of PI3K has also been shown to mediate axon retraction and growth cone collapse in response to semaphorin 3A. However, the effects of inhibiting PI3K on the neuronal cytoskeleton are not well characterized. We have previously reported that semaphorin 3A-induced axon retraction involves activation of myosin II, the formation of an intra-axonal F-actin bundle cytoskeleton, and blocks the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 30 publications
5
20
0
Order By: Relevance
“…In our own work on cultured sensory neurons, we have observed that spontaneously formed, and NGF-induced, axonal filopodia also emerge from transient accumulations of actin filaments in axons [ Fig. 4(A); Loudon et al, 2006;Gallo, 2006;Orlova et al, 2007;Ketschek and Gallo, 2010]. Similarly, Mingorance-Le Meur and O'Connor (2009) and Korobova and Svitkina (2008) also report that axonal filopodia emerge from focal accumulations of axonal actin filaments.…”
Section: The Formation Of Axonal Filopodiamentioning
confidence: 73%
See 1 more Smart Citation
“…In our own work on cultured sensory neurons, we have observed that spontaneously formed, and NGF-induced, axonal filopodia also emerge from transient accumulations of actin filaments in axons [ Fig. 4(A); Loudon et al, 2006;Gallo, 2006;Orlova et al, 2007;Ketschek and Gallo, 2010]. Similarly, Mingorance-Le Meur and O'Connor (2009) and Korobova and Svitkina (2008) also report that axonal filopodia emerge from focal accumulations of axonal actin filaments.…”
Section: The Formation Of Axonal Filopodiamentioning
confidence: 73%
“…actin patches (Lau et al, 1999). In peripheral sensory neurons (Loudon et al, 2006;Gallo, 2006;Orlova et al, 2007;Ketschek and Gallo, 2010) and central nervous system neurons (Mingorance-Le Meur and O'Connor, 2009), only a fraction of actin patches spontaneously give rise to filopodia. As determined by PREM (Svitkina, 2007) actin patches in sensory axons represent accumulation of actin filaments in a meshwork type of organization ( Fig.…”
Section: The Formation Of Axonal Filopodiamentioning
confidence: 99%
“…PI3K is an established component of the Sema3A signaling pathway (Atwal et al, 2003;Chadborn et al, 2006;Cosker and Eickholt, 2007;Orlova et al, 2007). Sema3A inactivates PI3K, and PI3K inactivation contributes to the collapse of sensory growth cones.…”
Section: Inactivation Of Pi3k By Semaphorin 3a Mediates the Loss Of Ementioning
confidence: 99%
“…Suppression of the basal activity of phosphatidylinositol 3-kinase (PI3K) is known to be required for Sema3A-induced growth cone collapse and neurite retraction (Chadborn et al, 2006;Orlova et al, 2007). Interestingly, PI3K is also known as a mediator of macropinocytosis (Swanson and Watts, 1995).…”
Section: Sema3a Signaling Decreases Syx1b Protein Levelmentioning
confidence: 99%